2021
DOI: 10.1007/s40593-021-00266-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Adults with Low Literacy Skills Interacting with an Intelligent Tutoring System

Abstract: A common goal of Intelligent Tutoring Systems (ITS) is to provide learning environments that adapt to the varying abilities and characteristics of users. This type of adaptivity is possible only if the ITS has information that characterizes the learning behaviors of its users and can adjust its pedagogy accordingly. This study investigated an intelligent tutoring system with computer agents (AutoTutor) designed to improve comprehension skills in adults with low reading literacy. One goal of this study was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…The literature on flipped learning has strongly emphasized the need for connection (Bergmann & Sams, 2014;Straw et al, 2015;Talbert, 2017), and we found that AI can serve as an assistant to support collaborative learning practices (Lechuga & Doroudi, 2022). For example, AI helped teachers create student groups or cohorts (Lechuga & Doroudi, 2022), provided meaningful feedback automatically to large student cohorts (Pardo et al, 2019), and classified clusters of learners so the instructor could adjust the learning environment based on their abilities and characteristics (Fang, Lippert, et al, 2021). In another case, machine learning models helped classify students' discussion content to determine if they were course relevant in an online discussion activity of blended learning using a problem-based learning pedagogy (Liao & Wu, 2022).…”
Section: Contributions Of Ai In Blended Learningmentioning
confidence: 79%
See 4 more Smart Citations
“…The literature on flipped learning has strongly emphasized the need for connection (Bergmann & Sams, 2014;Straw et al, 2015;Talbert, 2017), and we found that AI can serve as an assistant to support collaborative learning practices (Lechuga & Doroudi, 2022). For example, AI helped teachers create student groups or cohorts (Lechuga & Doroudi, 2022), provided meaningful feedback automatically to large student cohorts (Pardo et al, 2019), and classified clusters of learners so the instructor could adjust the learning environment based on their abilities and characteristics (Fang, Lippert, et al, 2021). In another case, machine learning models helped classify students' discussion content to determine if they were course relevant in an online discussion activity of blended learning using a problem-based learning pedagogy (Liao & Wu, 2022).…”
Section: Contributions Of Ai In Blended Learningmentioning
confidence: 79%
“…As another unique case, Méndez and González (2013) coined the term reactive blended learning to highlight the reactive feature of AI technology as applied in blended learning. Fang, Lippert, et al (2021) referred to it as hybrid intervention since their research practice consisted of a human teacher-led session and auto tutor session. Although the context studied by Ng and Chu (2021) was online learning only instead of blended learning, we considered it blended learning since the practices were a combination of asynchronous learning and F2F synchronous learning.…”
Section: Research Trends Related To Ai In Blended Learningmentioning
confidence: 99%
See 3 more Smart Citations